2020
DOI: 10.1002/mop.32570
|View full text |Cite
|
Sign up to set email alerts
|

A compact ultra‐wideband transverse electromagnetic mode horn antenna for high power microwave applications

Abstract: A compact ultra-wideband transverse electromagnetic mode (TEM) horn antenna for high power microwave (HPM) application is proposed. The designed antenna is capable of transmitting ultra-wideband pulse signals without an electric breakdown. An exponentially tapered profile structure is used to match the characteristics impedance between the feed line and free space for wideband. It is fed by a 50 Ω N-type connector. The antenna operates between 2.7 GHz to 12.5 GHz frequency ranges. The simulated and measured re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A time and frequency model approach for analysis of UWB antennas in general has been reported in Duroc et al 14 Design of TEM horn along with its optimization for GPR applications is reported in Jamali and Marklein 15 and Tan et al 16 Effect of aperture matching through addition of cylindrical sections at the TEM horn aperture is discussed for 0.5–7 GHz frequency range in Singh and Sarkar 17 . A half TEM horn antenna for 5 ns rise time pulse is reported by Umbarkar et al 18 TEM horn antenna used for near field microwave imaging in the frequency range of 3–10 GHz is reported in Reza et al 19 A modified TEM horn antenna with segmented structure for oil well monitoring in frequency range of 1.4–11 GHz is reported in Oloumi et al 20 A novel ultra‐wideband combined antenna for a frequency band of 0.18–30 GHz, which is a combination of TEM horn and magnetic dipole has been discussed in Mehrdadian et al 21 An irregular TEM horn with artificial dielectric for 1–10 GHz frequency band is reported in Ashikhmin et al 22 A compact high‐power UWB antenna with exponential taper is discussed in Yadav and Chittora 23 . In most of the literature available on TEM horn antennas, either frequency domain results or time domain results are discussed for high‐power systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A time and frequency model approach for analysis of UWB antennas in general has been reported in Duroc et al 14 Design of TEM horn along with its optimization for GPR applications is reported in Jamali and Marklein 15 and Tan et al 16 Effect of aperture matching through addition of cylindrical sections at the TEM horn aperture is discussed for 0.5–7 GHz frequency range in Singh and Sarkar 17 . A half TEM horn antenna for 5 ns rise time pulse is reported by Umbarkar et al 18 TEM horn antenna used for near field microwave imaging in the frequency range of 3–10 GHz is reported in Reza et al 19 A modified TEM horn antenna with segmented structure for oil well monitoring in frequency range of 1.4–11 GHz is reported in Oloumi et al 20 A novel ultra‐wideband combined antenna for a frequency band of 0.18–30 GHz, which is a combination of TEM horn and magnetic dipole has been discussed in Mehrdadian et al 21 An irregular TEM horn with artificial dielectric for 1–10 GHz frequency band is reported in Ashikhmin et al 22 A compact high‐power UWB antenna with exponential taper is discussed in Yadav and Chittora 23 . In most of the literature available on TEM horn antennas, either frequency domain results or time domain results are discussed for high‐power systems.…”
Section: Introductionmentioning
confidence: 99%
“…17 A half TEM horn antenna for 5 ns rise time pulse is reported by Umbarkar et al 18 TEM horn antenna used for near field microwave imaging in the frequency range of 3-10 GHz is reported in Reza et al 19 A modified TEM horn antenna with segmented structure for oil well monitoring in frequency range of 1.4-11 GHz is reported in Oloumi et al 20 A novel ultra-wideband combined antenna for a frequency band of 0.18-30 GHz, which is a combination of TEM horn and magnetic dipole has been discussed in Mehrdadian et al 21 An irregular TEM horn with artificial dielectric for 1-10 GHz frequency band is reported in Ashikhmin et al 22 A compact high-power UWB antenna with exponential taper is discussed in Yadav and Chittora. 23 In most of the literature available on TEM horn antennas, either frequency domain results or time domain results are discussed for high-power systems. Time domain analysis and frequency domain analysis along with experimental results for high-power UWB radiators is scarce.…”
mentioning
confidence: 99%
“…However, its HPM antenna has the defects of huge size and single-aperture radiation, so it is difficult to be used in highfrequency microwave devices. Common HPM antennas with a mode converter include Vlasov antennas [8][9][10], helical antennas [11][12][13], leaky waveguide antennas [14][15][16][17], horn antennas [18][19][20][21][22][23][24][25], parabolic reflector antennas [26,27], all-metal antenna [28,29] and EZ antennas [30,31]. The Vlasov antenna can generate a narrow radiation beam by configuring different circular waveguide opening shapes with a parabolic cylindrical reflector.…”
Section: Introductionmentioning
confidence: 99%